The role of lncRNAs in regulation of DKD and diabetes-related cancer - Cheng, Yawei; Wu, Xiaowen; Xia, Yujie; Liu, Wenjun; Wang, Peter (Frontiers in Oncology, 2022)
Diabetes mellitus often results in several complications, such as diabetic kidney disease (DKD) and end-stage renal diseases (ESRDs). Cancer patients often have the dysregulated glucose metabolism. Abnormal glucose metabolism can enhance the tumor malignant progression. Recently, lncRNAs have been reported to regulate the key proteins and signaling pathways in DKD development and progression and in cancer patients with diabetes. In this review article, we elaborate the evidence to support the function of lncRNAs in development of DKD and diabetes-associated cancer. Moreover, we envisage that lncRNAs could be diagnosis and prognosis biomarkers for DKD and cancer patients with diabetes. Furthermore, we delineated that targeting lncRNAs might be an alternative approach for treating DKD and cancer with dysregulated glucose metabolism.